I publish in I edit?--Do editorial board members of urologic journals preferentially publish their own scientific work? - Jens Mani; Jasmina Makarević; Eva Juengel; Hanns Ackermann; Karen Nelson; Georg Bartsch; Axel Haferkamp; Roman A Blaheta (PLoS ONE, 2013)
Scientists who are members of an editorial board have been accused of preferentially publishing their scientific work in the journal where they serve as editor. Reputation and academic standing do depend on an uninterrupted flow of published scientific work and the question does arise as to whether publication mainly occurs in the self-edited journal. This investigation was designed to determine whether editorial board members of five urological journals were more likely to publish their research reports in their own rather than in other journals. A retrospective analysis was conducted for all original reports published from 2001-2010 by 65 editorial board members nominated to the boards of five impact leading urologic journals in 2006. Publications before editorial board membership, 2001-2005, and publications within the period of time as an editorial board member, 2006-2010, were identified. The impact factors of the journals were also recorded over the time period 2001-2010 to see whether a change in impact factor correlated with publication locality. In the five journals as a whole, scientific work was not preferentially published in the journal in which the scientists served as editor. However, significant heterogeneity among the journals was evident. One journal showed a significant increase in the amount of published papers in the 'own' journal after assumption of editorship, three journals showed no change and one journal showed a highly significant decrease in publishing in the 'own' journal after assumption of editorship.